A modular-architecture controller for CNC systems based on open-source electronics. (July 2017) - Correa, Jorge E.; Toombs, Nicholas; Ferreira, Placid M.
Abstract: Open control architectures regain relevance with the new revolution of open source electronics. This paper presents the general ideas, examples of implementation and latest advances of a new, open architecture controller for CNC systems based on open source electronics. The multiprocessor and distributed architecture of this controller leverages the power of platforms like Arduino or TI Launchpad to realize CNC systems of increased computational resources, closed-loop position of the tool, smoother motions and higher feeds. Additionally, this work demonstrates the first steps in the development of virtual machine as a new software component of the architecture. A "tight binding" between the real and virtual machines will delineate the path for realistic, machine monitoring, remote operation and process planning environment.